Tourist Colonisers and the Colonisation of Available Recreational Space to the West of Łódź - Szkup, Roman (Turyzm/Tourism, 2003)
The article presents the demographic, social and spatial characteristics of the colonisers of available recreational space to the west of Łódź. The descriptions are based on a survey carried out among owners of plots who are treated as being representative. One method for modelling the 'spatial migration' of the places of permanent residence of the owners over time was innovation diffusion.